The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1371/journal.pone.0235597
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the future of land use and food security: A new set of global scenarios

Abstract: ecological crisis combined with social and economic crises, is still possible. Both scenarios should be part of the debate as the current context of the COVID-19 pandemic shows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 73 publications
2
34
0
1
Order By: Relevance
“…Identify drivers. Scenario development experts (L. Rutting and J. Vervoort) reviewed a wide range of existing scenario exercises (Alexandratos and Bruinsma 2012;CCAFS 2014;Gallopin et al 1997;IPCC 2000IPCC , 2013Mora et al 2016;OECD 2009;Palazzo et al 2016;Rockefeller Foundation and GBN 2010;Vervoort et al 2016;Vervoort et al 2013) and identified the drivers considered in these future scenarios. This preliminary list of drivers was refined by all participants prior to the workshop and also during the scenario workshop.…”
Section: Scenarios Developmentmentioning
confidence: 99%
“…Identify drivers. Scenario development experts (L. Rutting and J. Vervoort) reviewed a wide range of existing scenario exercises (Alexandratos and Bruinsma 2012;CCAFS 2014;Gallopin et al 1997;IPCC 2000IPCC , 2013Mora et al 2016;OECD 2009;Palazzo et al 2016;Rockefeller Foundation and GBN 2010;Vervoort et al 2016;Vervoort et al 2013) and identified the drivers considered in these future scenarios. This preliminary list of drivers was refined by all participants prior to the workshop and also during the scenario workshop.…”
Section: Scenarios Developmentmentioning
confidence: 99%
“…Diverse methodological approaches have been applied to develop extended SSPs at the global and regional scales and with different thematic foci and time scales. At the global scale, the Agrimonde-Terra scenarios couple a qualitative approach based on morphological analysis ( Ritchey, 2011 ) and a quantitative modeling approach to explore land use and food security in 2050 ( Mora and de Lattre-Gasquet, 2018 ; Mora et al, 2020 ). Similarly, Lenzner et al (2019) propose to combine stakeholder engagement and numerical models to derive scenarios on biological invasions for the 21 st century.…”
Section: Introductionmentioning
confidence: 99%
“…However, with the occurrence of the pandemic, an expressive portion of the population has been plunged into a state of extreme poverty, a result of the interaction between a history of structural, social and economic inequality and the expressive contingent of informal or unemployed workers, enhanced by the precarious conditions of the food production and commercialisation system, which involves agribusiness, a complex system of economic interests of large global groups (1,2) . These conditions are intensified by the impact of the fight for land, restricted access to drinking water and natural disasters with effects on the climate and the scarcity or lack of rain in many geographical regions of the planet (3) .…”
mentioning
confidence: 99%